KAJIAN UPAYA HUKUM KASASI TERHADAP PUTUSAN LEPAS TINDAK PIDANA PENGANIAYAAN (STUDI PUTUSAN NO. 810/K/PID/2014) - Tsavier Yufa Aqya (Sebelas Maret University, 2023)
This research aims to find out the suitability of the Supreme Court’s consideration in granting the Cassation request by the Public Prosecutor with Article 256 of Criminal Procedure Code. This type of research is normative legal research that is prescriptive and applied to case studies. The technique of collecting primary and secondary legal materials used for this study is documental study and literature materials. Based on the result and discussion define the Supreme Court Judge’s consideration in examining and adjudicate the Public Prosecutor’s Cassation request stating that granting the Public Prosecutor’s Cassation request, cancelling the Sleman District Court Decision Number 25/Pid.B/2014/PN.SLMN and adjudicate itself stated that the defendant Elly Ratna Pritawaty had been legally and convincingly proven guilty of committing the crime of prosecution and sentenced her to imprisonment for 4 (four) months in accordance with the provisions contained in Article 256 of the Criminal Procedure Code. The judge’s consideration in accepting or granting the cassation request in this persecution case has fulfilled the provision in Article 351 of the Criminal Code. The judge has described the facts found at trial which can strengthen the judge's argument. The judge was of the opinion that the Panel of Judges of the Sleman District Court had made a mistake in applying the legal regulations as they should. Whereas the Panel of Judges at the Sleman District Court stated that the defendant had been proven guilty of committing the crime of persecution. However, the act was carried out in self-defence because the victim immediately attacked the victim and swung his shoe at the defendant's face. Keywords: Legal Effort, Cassation, Persecution, Acquittal